2005
DOI: 10.1262/jrd.17025
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Competence of HMC Derived Bovine Cloned Embryos Obtained from Somatic Cell Nuclear Transfer of Adult Fibroblasts and Granulosa Cells

Abstract: Abstract. To enable us to handle a large number of oocytes at a given time and to have an increased throughput of cloned embryos, we attempted the Handmade cloning (HMC TM ) technique, a zona-free method of bovine somatic cell nuclear transfer. Our objective was to study the developmental competence of the HMC TM derived embryos obtained using different types of somatic cells. A total of 6,874 cumulus-oocyte-complexes were used with either 7th or 11th passage fibroblasts (1st and 2nd groups, respectively), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
9
1
2
Order By: Relevance
“…In our previous studies [16,18], we demonstrated successful application of the HMC TM method in our laboratory. In spite of our continued success in carrying out NT experiments, we frequently encounter huge variations in blastocyst rates.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In our previous studies [16,18], we demonstrated successful application of the HMC TM method in our laboratory. In spite of our continued success in carrying out NT experiments, we frequently encounter huge variations in blastocyst rates.…”
Section: Discussionmentioning
confidence: 88%
“…Both the classic procedure [2] and the still relatively new method of handmade cloning (HMC TM ) [23,16] have led to live offspring. However, both techniques are problematic because they require resetting of the gene expression program of somatic cells to that consistent with early embryonic development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of development to blastocysts as well as the efficiency of birth of healthy animals is not different when embryos were produced by HMC compared with the conventional procedure (Bhojwani et al 2005, Lagutina et al 2007. Currently, several groups are using HMC as the first alternative to generate cloned animals from different species.…”
Section: Introductionmentioning
confidence: 99%